Development and implementation of a national online application system for cross-jurisdictional linked data - Wray, Natalie; Miller, Kate; Irvine, Katie; Moore, Elizabeth; Crisp, Alice; Bapaume, Kathleen; Taylor, Catherine; Smetak, Rob; Wiggins, Nadine; Dombrovskaya, Mikhalina; Flack, Felicity (International Journal of Population Data Science, 2022)
The Population Health Research Network (PHRN) is an Australian national data linkage infrastructure that links a wide range of health and human services data in privacy-preserving ways. The data linkage infrastructure enables researchers to apply for access to routinely collected, linked, administrative data from the six states and two territories which make up the Commonwealth of Australia, as well as data collected by the Australian Government. The PHRN is a distributed network where data is collected and managed at the respective jurisdictional and/or cross-jurisdictional levels. As a result, access to linked data from multiple jurisdictions requires complex approval processes. This paper describes Australia's approach to enabling access to linked data from multiple jurisdictions. It covers the identification of, and agreement to, a minimum set of data items to be included in a unified national application form, the development and implementation of a national online application system and the harmonisation of business processes for cross-jurisdictional research projects. Utilisation of the online application system and the ongoing challenges of data linkage across jurisdictions are discussed. Changes to the data custodian and ethics committee approval criteria were out of scope for this project.